Pencegahan Perundungan dan Kekerasan Seksual (PPKS) pada Mahasiswa Baru di Sekolah Tinggi Ilmu Ekonomi Totalwin - Maulana Ihsan Yusufi Suyatno; Anisa Kusumawardani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Efforts to prevent bullying and sexual violence in higher education institutions are increasingly urgent due to their significant psychological, social, and academic impacts on students. New students are particularly vulnerable as they undergo a transition period of social and environmental adaptation within campus life. This community service program aimed to enhance students’ knowledge, awareness, and preventive capacity regarding bullying and sexual violence.The program employed participatory educational methods consisting of lectures, small-group discussions, role-playing simulations, and evaluative reflection. Participants were new students of Totalwin School of Economics from diverse regional and socio-cultural backgrounds. Evaluation results indicated that approximately 90% of participants demonstrated improved comprehension of definitions, forms, impacts, and prevention mechanisms of bullying and sexual violence. In addition, simulation-based learning significantly strengthened students’ confidence in responding appropriately to real-life risk situations.Despite several implementation challenges such as limited session duration, uneven participation, and discomfort in discussing sensitive issues the program effectively fostered collective awareness and encouraged the development of a safer and more inclusive campus culture. Sustainable follow-up programs, institutional collaboration, and integration of psychological and legal support services are recommended to ensure long-term impact.